2010
DOI: 10.1075/lia.1.1.08cou
|View full text |Cite
|
Sign up to set email alerts
|

Évaluer les compétences linguistiques des enfants en langue des signes française

Abstract: Devant l’absence de test d’évaluation des aptitudes linguistiques en langue des signes française (LSF) des enfants signeurs et les besoins exprimés par les nombreux professionnels et chercheurs concernés, nous avons tenté d’adapter à la LSF un test déjà validé pour une autre langue des signes. Notre choix s’est porté sur le test de BSL de Herman et al. (1999), car son usage est relativement simple et peut être utilisé tant pour les besoins de la recherche que par les professeurs de/en LSF. Les résultats obtenu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The LSF RST’s authors (Courtin et al., 2010) also faced problems with the linguistic category of negation: LSF seems to contain fewer negation structures than BSL. Courtin et al. (2010) highlighted that in the BSL RST, negation features are assessed in 10 items out of 40 (25%).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The LSF RST’s authors (Courtin et al., 2010) also faced problems with the linguistic category of negation: LSF seems to contain fewer negation structures than BSL. Courtin et al. (2010) highlighted that in the BSL RST, negation features are assessed in 10 items out of 40 (25%).…”
Section: Discussionmentioning
confidence: 99%
“…However, no measure to assess deaf children’s knowledge of PJM is available. Analysing RST validity, Johnston (2004) and Courtin et al. (2010) suggested that it is possible that the RST does not measure sign language skills but instead more general visuo-spatial skills since there are a large number of items testing sign language features with high iconicity (Courtin et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations